(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores the nonverbal dimensions of expressing affirmation and negation through a psycholinguistic and communicative lens. While much of linguistic research has traditionally focused on verbal structures, this study emphasizes the significant role that gestures, facial expressions, body posture, and eye movements play in conveying agreement or disagreement. Drawing on contemporary theories in psycholinguistics and communication studies, the paper argues that nonverbal cues are not merely supplementary to verbal statements but function as independent semiotic systems capable of carrying nuanced meaning. The study highlights cultural variability in nonverbal expression, demonstrating that similar gestures can carry different pragmatic loads across languages and societies. Through analysis of cross-cultural examples and experimental observations, the paper uncovers how cognitive processing of nonverbal affirmation and negation influences interpersonal understanding, particularly in contexts where verbal communication is limited or ambiguous. It concludes that the integration of nonverbal analysis is essential for a comprehensive understanding of how humans express truth-values, social attitudes, and emotional stances.